Recent progress in 3D printing degradable polylactic acid‐based bone repair scaffold for the application of cancellous bone defect - Hu, Xulin; Lin, Zhidong; He, Jian; Zhou, Minchang; Yang, Shuhao; Wang, Yao; Li, Kainan (MedComm - Biomaterials and applications, 2022)
Large size bone defects have become a growing clinical challenge. Cancellous bone, which has the highest volume ratio, the fastest replacement rate, and interconnected porous structure, plays a major role in bone repairing. Considering the structure and composition of cancellous bone, building a bionic 3D scaffold via customized‐3D printing technology is the key to solving the problem. As the earliest degradable medical polymer material approved by Food and Drug Administration, polylactic acid has been proved to have excellent biosafety and can be copolymerized or blended with other synthetic polymers, natural polymers, and inorganic materials to improve its performance to better meet clinical applications. A series of biodegradable bone repair scaffolds based on polylactic acid composites and 3D printing technology are developed to achieve large bone defects. Here, we review the composition and structure of cancellous bone, highlighting the relationship to the requirements of bone repair scaffolds. The different types of polylactic‐acid‐based materials applied in 3D printing technology are described, emphasizing the connection between materials, preparation methods, and applications. This paper reviews the application of 3D printing biodegradable polylactic acid based materials in cancellous bone repair. Starting from the structure of cancellous bone, and then summarizes the classification of polylactic acid mixed with different types of biodegradable materials to combination with the implementation of 3D printing technology